Studies on interfaith relations: latest input for Authority Management Review (AMR) in Malaysia - Syed Ismail al-Qudsy, Sharifah Hayaati; Abdul Majid, Mahmood Zuhdi; Yousif, Ahmed F; Abdullah @ Chuah Hock Leng, Osman; Abdul Mutalib, Marina Munira (Routledge, Taylor & Francis Group, 2016)
Malaysia is a multi-religious society with 28.3 million people. The country had succeeded in managing religious diversity for almost fifty-seven years. This includes the promotion of interfaith relationships granted under the right to religious freedom, which is protected by the State. There are, however, emerging interfaith challenges, including conversion from one faith to another and reversion back to the original faith, these types of challenges appearing especially in the early millennium. This article reviews the ten latest research studies on interfaith issues in Malaysia and identifies useful themes for authority in exercising management review. Using the content analysis method, this study found that there are several important managerial aspects to be taken into serious consideration, including setting clear parameters for freedom of religion in Malaysia, clear procedures for managing religious conflict, managing faith with respect, and effectively promoting media advocacy. The findings also give insights on the development of interfaith studies in Malaysia.